Laser parameter variations in a rayleigh scattering-based raman fiber laser with single fiber bragg grating reflector - Sarmani, A.R.; Abu Bakar, M.H.; Adikan, Faisal Rafiq Mahamd; Mahdi, M.A. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
The work presented in this paper details the changes in continuous-wave laser characteristics that were affected by the orientation of pumping separation. The Raman laser was constructed in forward and backward pumping schemes with respect to the 1553.3-nm fiber Bragg grating location. The laser cavity was formed by the induction of Rayleigh backscattering effects in the 51-km fiber length that served as a virtual mirror. From the results obtained, it can be concluded that low threshold operation around 788 mW was satisfied at a coupling ratio of 0 (forward pumping scheme). Moreover, the best output power attainment of 220 mW was realized when 60 of pump powers were delivered via a backward pumping scheme. Thus, the success of this research provides a basis to further understand the principle of backscattered wave interactions along the fiber longitudinal structure.